2 - African Feminist Epistemic Communities: Keynote Address Presented at the Reflections Meeting on the CODESRIA Gender Institutes: Pasts and Futures Kampala, Uganda, 7 June 2023 - Okech, Awino (CODESRIA Bulletin, 2023)